Reservoir flood regulation affects nutrient transport through altering water and sediment conditions. (15th April 2023) - Tang, Xianqiang; Li, Rui; Wang, Danyang; Jing, Zheng; Zhang, Wei
Highlights: Reservoir flood regulation traps a great deal of suspended sediment. Phosphorus trapped with sediment while nitrogen flows downstream with water. Causing TN/TP ratio correspondingly increases from tail to head of reservoir. Flood regulation affects nutrient through altering water and sediment conditions. Abstract: The effect of reservoir construction on nutrient dynamics is well recognized, at flood event-scale influence of reservoir flood regulation on nutrient transport however has received less attention. Taking the Three Gorges Reservoir (TGR) in the Changjiang River as an example, during the TGR's regulation on a flood in Sep., 2021, this study collected water samples along the mainstream of the reservoir as well as pre/post-dam, with the aim to identify the impact of flood regulation on nutrient (nitrogen and phosphorus) distribution and transportation. Results show that nitrate nitrogen (NO3 N) and particulate phosphorus (PP) were the main fraction of the total nitrogen (TN) and total phosphorus (TP) with the proportion of 46.5%-95.6% and 57.4%-81.6%, respectively. N and P responded different to flood regulation: (i) along the stream P concentration significantly decreased due to PP deposited with sediment while N concentration barely changed during flood regulation; (ii) P concentration was significantly higher at post-dam section than at pre-dam section, while N concentration maintained the same. The diffed response to flood regulation caused TN/TP ratio increased from 4 to 8 in the reservoir tail to over 20 near the dam, which probably arise eutrophication in the reservoir head area. This study reveals the influence of flood regulation on nutrient transport in flood event and provides scientific basis for reservoir management. Graphical abstract: Image, graphical abstract